PEDAGOGICAL CULTURE OF FUTURE MILITARY OFFICERS: THE PROBLEM OF SEPARATING THE STRUCTURAL COMPONENTS OF THE PHENOMENON (Physical Culture and Sport: Scientific Perspective, 2023)
The article analyzes the phenomenon of pedagogical culture in future military officers from the perspective of its complexity, versatility, and multi-functionality. It has been found that the pedagogical culture of future military officers reflects the extent to which they have mastered the unique experience of training and educating their service personnel. This experience is integrated into the nation's and society's historical development, the advanced achievements of international and national pedagogical science and practice, pedagogy traditions, and the social meanings of educational activities. This study aims to specify the structural components of the pedagogical culture of future military officers based on the existing findings in the theory and practice of pedagogical science. The following tasks have been accomplished to achieve the stated goal: to analyze the meaning of "pedagogical culture of future military officers"; to identify the substantive vectors of its deployment in the military and professional activities of a modern officer; to specify the components of the pedagogical culture of future military officers. While performing these tasks, the authors applied such methods of scientific cognition as analysis, synthesis, comparison, and generalization. Research results. Pedagogical culture is a feature of a specific subject of military-pedagogical activity. It reflects the extent to which they are familiar with society's substantive pedagogical culture and socio-professional group. Pedagogical culture is an independent pedagogical phenomenon that determines the parameters of pedagogical activity of a particular subject of military and professional activity. The pedagogical culture of future military officers was interpreted as an integrative personal feature that reflects the ability to use the substantive pedagogical culture of society and their socio-professional group in military and pedagogical activities, as well as in their own development as a subject of these activities.The authors have determined that the pedagogical culture of future military officers describes their mastery of ideas and traditions of military pedagogy, military pedagogical technologies, etc. This culture is a part of the pedagogical culture of their socio-professional group. That constitutes an officer's specific subcultural array of knowledge, skills, and abilities. As part of the military professional culture, the pedagogical culture of future military officers reflects their stance on the pedagogical component of military professional activity, their mastery and utilization of the meanings of military professional activity, and, in particular, the training and education of military personnel. The structure of the studied phenomenon intertwines and closely interacts with various components. These components should be specified in four interconnected components: "motivation and value," "cognitive," " active and ethical," and " personal development"). Each component integrates certain indicators (professional motivation, need to expand military pedagogical knowledge, interest in developing personal awareness in the field of military pedagogy, military and pedagogical orientation, pedagogical beliefs of the future officer, pedagogical thinking, formed professionally significant properties of the officer-teacher, pedagogical optimism, pedagogical skills, culture of pedagogically oriented communication and behavior awareness of the importance of self-education in the direction of mastering modern achievements of military pedagogy). The complexity within the pedagogical culture of future military officers demonstrates the necessity of updating and strengthening the process of cadets' professional training in higher military educational institutions.
Keywords: future military officers; pedagogical culture; components; pedagogical skills; service members; pedagogical thinking